Alpha- and beta-band oscillations subserve different processes in reactive control of limb movements - Pani, Pierpaolo; Di Bello, Fabio; Brunamonti, Emiliano; D’Andrea, Valeria; Papazachariadis, Odysseas; Ferraina, Stefano (Frontiers in Behavioral Neuroscience, 2014)
The capacity to rapidly suppress a behavioral act in response to sudden instruction to stop is a key cognitive function. This function, called reactive control, is tested in experimental settings using the stop signal task, which requires subjects to generate a movement in response to a go signal or suppress it when a stop signal appears. The ability to inhibit this movement fluctuates over time: sometimes, subjects can stop their response, and at other times, they can not. To determine the neural basis of this fluctuation, we recorded local field potentials (LFPs) in the alpha (6-12 Hz) and beta (13-35 Hz) bands from the dorsal premotor cortex of 2 nonhuman primates that were performing the task. The ability to countermand a movement after a stop signal was predicted by the activity of both bands, each purportedly representing a distinct neural process. The beta band represents the level of movement preparation; higher beta power corresponds to a lower level of movement preparation, whereas the alpha band supports a proper phasic, reactive inhibitory response: movements are inhibited when alpha band power increases immediately after a stop signal. Our findings support the function of LFP bands in generating the signatures of various neural computations that are multiplexed in the brain.